Transient Temperature Distribution of Underground Carbon Dioxide Salt Cavern Storage With State Space Model - Yuan, Zhou; Zhou, Yanxi; Wei, Minghui; Liao, Xinwei (Frontiers in Energy Research, 2020)
Underground salt cavern has become one of the potential means for Carbon Dioxide(CO2) storage due to it has some advantages, such as high storage capacity and easy construction and so on. The wellbore and salt cavern heat transfer models for CO2 injection process is developed, which is solved by the state space method. The results indicate that the temperature of annulus and salt cavern are significantly influenced by the injection rate during the injection process, and the fluids temperature in tubing remains approximately constant. When the injection process stops, the temperature of annulus and salt cavern are dominated by the formation temperature. The change of tubing fluids temperature mainly occurs after the process of injection stops for a few hours, which would cause crystal separate out from the fluids. This result can also explain why the tubing may be blocked after the gas injection stops.